FENNEL YIELD AND QUALITY DEPENDING ON TECHNOLOGICAL FACTORS IN THE CONDITIONS OF FOREST-STEPPE OF UKRAINE - Хоміна, В. Я.; Строяновський, В. С. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The growth of the essential oils market is explained by the growing demand for natural and organic products. Today, the global aromatherapy market with essential oils is growing, and demand for essential oils is increasing at the same rate. The studies are dedicated to the valuable essential oil culture ‒ fennel, the spread of which in the forest-steppe zone of Ukraine will allow to obtain high profitability by agro-forming of different forms of ownership and will help to provide the Ukrainian market with raw materials of appropriate quality. The article offers a solution to the pressing issue of expanding the area of new unconventional culture in the conditions of the Forest-Steppe of Ukraine by improving technological measures in the cultivation of culture. The basis of scientific research is the study of sowing terms (1st decade of April, for soil LTR 6-80C), (2nd decade of April, for LTR of soil 10-120C); row spacing (5, 30, 45 and 60 cm) and seeding rates (1, 1.5 and 2 million sprouting seeds per hectare). Among the plans of the research tasks were: to conduct the accounting of yields and to determine indicators of seeds quality (the content of essential oil in fennel seeds and its conditional yield per hectare of sowing), depending on the studied factors. Crop accounting was performed by continuous submerged threshing. The yield was brought to 100% purity and standard humidity according to the method described by V.O. Moiseychenko and V.O. Yeshchenko. Mathematical data processing was performed according to the method of B.A. Dopehova. The results of the research show that the sowing variants in the first decade of April, with a wide-row method (45 cm) sowing rate of one million sprouting seeds per hectare, yielded the optimum yield of fennel – 1.48 t / ha. In the same variant, the maximum content of essential oil was obtained – 6.23% and its yield from the hectare sowing area‒ 59.2 kg.